2008
DOI: 10.1007/s10532-008-9231-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesophilic and thermophilic anaerobic co-digestion of abattoir wastewater and fruit and vegetable waste in anaerobic sequencing batch reactors

Abstract: Anaerobic co-digestion of fruit and vegetable waste (FVW) and abattoir wastewater (AW) was investigated using anaerobic sequencing batch reactors (ASBRs). The effects of hydraulic retention time (HRT) and temperature variations on digesters performances were examined. At both 20 and 10 days biogas production for co-digestion was greater thanks to the improved balance of nutrients. The high specific gas productions for the different digestion processes were 0.56, 0.61 and 0.85 l g(-1) total volatile solids (TVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 30 publications
2
23
0
3
Order By: Relevance
“…Two stage digestion of mixture of activated sludge and fruit/ vegetable wastes resulted in a methane content of 68 % [21]. ASBR were utilized for the anaerobic co-digestion of abattoir wastewater and fruit/vegetable wastes at HRT of 10 and 20 days [13].…”
Section: Waste To Bioenergymentioning
confidence: 99%
“…Two stage digestion of mixture of activated sludge and fruit/ vegetable wastes resulted in a methane content of 68 % [21]. ASBR were utilized for the anaerobic co-digestion of abattoir wastewater and fruit/vegetable wastes at HRT of 10 and 20 days [13].…”
Section: Waste To Bioenergymentioning
confidence: 99%
“…Meat product wastes are also an excellent source of labile carbon (Bouallagui et al 2009) and consequently, abattoir wastes would be ideal organic materials for sulfate reduction. This was not an option as the greater Pilbara study region does not have an abattoir; the region's cattle industry primarily involves live export, or live transportation to south-western WA slaughter yards.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, they proposed a protocol to improve the start-up phase for dry thermophilic anaerobic digestion of FW. The study of Bouallagui et al (2009) observed a maximum OLR of 1.24 kg VS m −3 day −1 operating a thermophilic anaerobic sequencing batch reactor (ASBR) treating FVW with a 15-day HRT. They achieved a high biogas yield of 0.48 m 3 kg −1 VS added with 60 % methane content and a 79 % VS reduction.…”
Section: Production Of Biogas By Anaerobic Digestion Processesmentioning
confidence: 99%
“…They achieved a high biogas yield of 0.48 m 3 kg −1 VS added with 60 % methane content and a 79 % VS reduction. In a similar study, Bouallagui et al (2009) examined the effect of HRT and temperature variations under mesophilic and thermophilic conditions on the performance of an ASBR treating abattoir waste water with FVW. They observed a volatile solid removal between 73 and 86 % and a biogas yield of about 0.3-0.73 m 3 kg −1 TVS added at OLRs up to 2.56 kg TVS m −3 day −1 in the ASBR codigestion process.…”
Section: Production Of Biogas By Anaerobic Digestion Processesmentioning
confidence: 99%